Gambaran Jumlah Leukosit dan Laju Endap Darah pada Penderita Penyakit Demam Berdarah Dengue (DBD) di Rumah Sakit Umum Wisata Universitas Indonesia Timur Makassar - MUH.Rizman Naim (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2017)
The number of cases of Dengue Hemorrhagic Fever (DHF) in the last six months continued to soar. Data obtained at the Health Office (Health Office) of Makassar City, the total number of patients who tested positive for Dengue Hemorrhagic Fever (DHF) was recorded 528 cases, throughout January 2016. The data shows a spike in every month.This study aims to determine the results of the examination of the number of leukocytes and Blood Endap Rate in patients with Dengue Hemorrhagic Fever (DBD) in General Hospital Tourism University of Eastern Indonesia Makassar. The type of research is a laboratory observation that is described descriptively ie to perform blood tests on Dengue Hemorrhagic Fever (DHF) patients so it is known that the results of examination of leukocyte count and blood vapor rate examination in Dengue Hemorrhagic Fever (DBD) patient. Based on the results of the examination on 10 samples of Dengue Hemorrhagic Fever (DHF) is obtained results 60% of the sample decreased the number of leukocytes with an average value of 17.8 and 40% of the sample leukositnya value of normal value with an average value of 25.7, 60% sedimentation rate of the sample had normal values ​​with an average value of 74 and 40% of the sample had an elevated sedimentation rate of blood with an average value of 60.For prospective researchers further suggested that researchers calculate the number of leukocytes and Blood Endap Rate using more samples and using other variables.